The scientific and research experiences in the implementation of the program “From the Land of Witelon to the Land of Ivan Franko” between 2019 and 2023 - Skwarek, Beata; Lazorak, Bohdan (Naukowo-badawcze doświadczenia w realizacji programu „Od ziemi Witelona do ziemi Iwana Franki” w latach 2019-2023, 2023)
In this article, the authors refer to their own experiences related to the implementation of the “From the Land of Witelon to the Land of Ivan Franko” program, which has been ongoing since 2019. The continuation of historical research is reflected in 2023 in a project funded from the state budget granted by the Minister of Education and Science under the “Science for Society II” Program.
Zeszyty Naukowe Collegium Witelona, nr 47(2)/2023, s. 19-26
Keywords: research; cultural heritage; history; projects; collaboration